Building social capital for stable employment: The postprison experiences of Black male exprisoners. Issue 3 (2nd April 2016) - Strickland, Joseph
ABSTRACT: This study examines whether and how Black male exoffenders take the support they receive from personal contacts and build social capital to get and maintain a job. Data were collected using in-depth, semistructured interviews with 20 formerly incarcerated males who were transitioning from state and federal prisons to Chicago, IL communities. The findings indicate that family members, including fictive kin, can provide valuable assistance that facilitates Black male former prisoners obtaining postprison employment.